Boosting CO2 Capture and Its Photochemical Conversion on Bismuth Surface. Issue 9 (9th March 2021) - Yin, Sheng; Zhong, Kang; Yu, Qing; Wang, Zhaolong; Li, Qidi; Feng, Ziyi; Du, Huishuang; Yang, Jinman; Hua, Yingjie; Zhu, Xingwang; Xu, Hui
Abstract : The activity and efficiency of photocatalytic CO2 conversion are limited by a narrow spectral response range and fast electron–hole pair recombination. As plasmonic photocatalysts have become novel catalytic materials for visible light, herein, a typical Bi2 O3 photocatalyst as a template to achieve simultaneous in situ bismuth reduction and coupling on the material surface via hydrogen–argon plasma alteration is used. Combining the surface plasmon resonance effect of Bi nanoparticles and the characteristics of composite photocatalytic materials, Bi–Bi2 O3 exhibits excellent efficiency in light absorption and separation of photogenerated carriers; photocatalytic activity is significantly enhanced. The CO yields are changed with plasma‐treated duration; the maximum is reached at a treatment time of 3 min, where the rate of CO production is 29.87 μmol h −1 g −1 and CH4 production rate increases from 0 to 6.29 μmol h −1 g −1 . The reaction mechanism is further confirmed by in situ Fourier‐transform infrared spectroscopy. Both the efficient light‐generated carrier separation and intense light absorption contribute to the high activity of the well‐designed Bi–Bi2 O3 catalyst. Abstract : In a mixed atmosphere of hydrogen and argon, bismuth oxide is processed by low‐temperature plasma technology, and part of bismuth oxide is reduced to Bi. Benefiting from the surface plasmon resonance effect of Bi nanoparticles, Bi–Bi2 O3 composite photocatalytic material exhibits excellent efficiency in light absorption and separation of photogenerated carriers; photocatalytic activity is significantly enhanced.